Mangosteen peel extract reduces formalin-induced liver cell death in rats - Afiana Rohmani; Sarjadi Sarjadi; Winarto Winarto; Kisdjamiatun Kisdjamiatun (Universa Medicina, 2014)
BACKGROUNDFormalin is a xenobiotic that is now commonly used as a preservative in the food industry. The liver is an organ that has the highest metabolic capacity as compared to other organs. Mangosteen or Garcinia mangostana Linn (GML) peel contains xanthones, which are a source of natural antioxidants. The purpose of this study was to evaluate the effect of mangosteen peel extract on formalin- induced liver cell mortality rate and p53 protein expression in Wistar rats.METHODSEighteen rats received formalin orally for 2 weeks, and were subsequently divided into 3 groups, consisting of the formalin-control group receiving a placebo and treatment groups 1 and 2, which were treated with mangosteen peel extract at doses of 200 and 400 mg/kgBW/day, respectively. The treatment was carried out for 1 week, and finally the rats were terminated. The differences in liver cell mortality rate and p53 protein expression were analyzed.RESULTSOne-way ANOVA analysis showed significant differences in liver cell mortality rate among the three groups (p=0.004). The liver cell mortality rate in the treatment group receiving 400 mg/kgBW/day extract was lower than that in the formalin- control group. There was no p53 expression in all groups.CONCLUSIONSGarcinia mangostana Linn peel extract reduced the mortality rate of liver cells in rats receiving oral formalin. Involvement of p53 expression in liver cell mortality in rats exposed to oral formalin is presumably negligible.